Letter (copy) : Goods for Spain - Tewson, Vincent
030-0128-001 Secretary's. HVT/FC/EK/1415. EXPORT ST/HP. 1179. 30th June, 1938. Mr. E. Winstanley, Export Department, The Co-operative Wholesale Society Limited, 1, Balloon Street, MANCHESTER. Dear Mr. Winstanley, GOODS FOR SPAIN. I thank you for your letter of the 29th June forwarding invoice amounting to £1212.10.0., which will receive our early attention. It is noted that the goods were consigned at the order of Mr. Calvert who has been instructed to effect delivery to Sr. Santiago. It is also noted that Sr. Santiago has been advised both by you and the actual sender of the milk of the dispatch of this consignment. Yours sincerely, Assistant Secretary. 292/946/30/128